BURKHOLDERIA PSEUDOMALLEI AS THE PREDOMINANT CAUSE OF SPLENIC ABSCESS IN KAPIT, SARAWAK, MALAYSIAN BORNEO - Chang, Chee Yik (Journal of Ayub Medical College Abbottabad, 2023)
Background: Splenic abscess is an uncommon condition, with autopsy studies estimating an incidence rate of 0.14-0.70%. Causative organisms can be extremely diverse. Burkholderia pseudomallei is the most common cause of splenic abscess in melioidosis-endemic areas. Methods: We reviewed 39 cases of splenic abscesses in a district hospital in Kapit, Sarawak, from January 2017 to December 2018. The demographics, clinical characteristics, underlying diseases, causative organisms, therapeutic methods, and mortality rates were investigated. Results: There were 21 males and 18 females (mean age, 33.7±2.7 years). Almost all patients (97.4%) had a history of pyrexia. Diabetes mellitus was present in 8 patients (20.5%). Splenic abscesses were diagnosed using ultrasonography and were multiple in all 39 cases. Positive blood cultures were obtained in 20 patients (51.3%), and all yielded B. pseudomallei. Melioidosis serology was positive in 9 of 19 patients (47.4%) with negative blood cultures. All patients were treated for melioidosis with antibiotics without the need for surgical intervention. All splenic abscesses resolved after anti-melioidosis treatment was completed. One patient died (2.6%) as a result of B. pseudomallei septicaemia with multiorgan failure. Conclusion: Ultrasonography is a valuable tool for diagnosing splenic abscesses in resource-limited settings. B. pseudomallei was the most common etiological agent of splenic abscesses in our study. Background: Splenic abscess is an uncommon condition, with autopsy studies estimating an incidence rate of 0.14-0.70%. Causative organisms can be extremely diverse. Burkholderia pseudomallei is the most common cause of splenic abscess in melioidosis-endemic areas. Methods: We reviewed 39 cases of splenic abscesses in a district hospital in Kapit, Sarawak, from January 2017 to December 2018. The demographics, clinical characteristics, underlying diseases, causative organisms, therapeutic methods, and mortality rates were investigated. Results: There were 21 males and 18 females (mean age, 33.7±2.7 years). Almost all patients (97.4%) had a history of pyrexia. Diabetes mellitus was present in 8 patients (20.5%). Splenic abscesses were diagnosed using ultrasonography and were multiple in all 39 cases. Positive blood cultures were obtained in 20 patients (51.3%), and all yielded B. pseudomallei. Melioidosis serology was positive in 9 of 19 patients (47.4%) with negative blood cultures. All patients were treated for melioidosis with antibiotics without the need for surgical intervention. All splenic abscesses resolved after anti-melioidosis treatment was completed. One patient died (2.6%) as a result of B. pseudomallei septicaemia with multiorgan failure. Conclusion: Ultrasonography is a valuable tool for diagnosing splenic abscesses in resource-limited settings. B. pseudomallei was the most common etiological agent of splenic abscesses in our study.